A Community-Driven Approach to Urban Waste Management: Insights from the Kenanga Waste Bank, Bogor, Indonesia - Al Zahra, Princessca; Shohibuddin, Mohamad (Society, 2025)
Urban waste management remains a pressing challenge in Indonesia, with Bogor City being among the highest waste-producing areas. Community-based waste banks offer a promising solution by promoting waste reduction, recycling, and economic incentives. This study examines the effectiveness of the Kenanga Waste Bank, a leading community initiative in RW 1 (Rukun Warga, or neighborhood unit), Babakan Subdistrict, Bogor City. Using a mixed-methods approach, the research combines surveys of 35 waste bank members, in-depth interviews, and observations to assess managerial performance, community participation, and socio-environmental benefits. Data analysis employed Spearman rank correlation and chi-square tests to explore key relationships between participation levels, governance structures, and financial sustainability. The findings reveal strong operational and institutional management but highlight gaps in waste-sorting enforcement and participation in decision-making. While economic and environmental benefits are recognized, financial sustainability remains a concern due to fluctuations in the recyclable market. Strengthening participatory governance, diversifying revenue sources, and enforcing waste-sorting practices are critical for long-term success. This study offers practical recommendations for policymakers, waste bank operators, and community leaders to enhance participation, improve governance, and integrate waste banks into formal waste management systems. By addressing these key challenges, waste banks can serve as scalable models for sustainable urban waste management in Indonesia.